Cholic acid therapy in Zellweger spectrum disorders - Berendse, Kevin (J Inherit Metab Dis, 2016)
INTRODUCTION: Zellweger spectrum disorders (ZSDs) are characterized by a failure in peroxisome formation, caused by autosomal recessive mutations in different PEX genes. At least some of the progressive and irreversible clinical abnormalities in patients with a ZSD, particularly liver dysfunction, are likely caused by the accumulation of toxic bile acid intermediates. We investigated whether cholic acid supplementation can suppress bile acid synthesis, reduce accumulation of toxic bile acid intermediates and improve liver function in these patients. METHODS: An open label, pretest-posttest design study was conducted including 19 patients with a ZSD. Participants were followed longitudinally during a period of 2.5 years prior to the start of the intervention. Subsequently, all patients received oral cholic acid and were followed during 9 months of treatment. Bile acids, peroxisomal metabolites, liver function and liver stiffness were measured at baseline and 4, 12 and 36 weeks after start of cholic acid treatment. RESULTS: During cholic acid treatment, bile acid synthesis decreased in the majority of patients. Reduced levels of bile acid intermediates were found in plasma and excretion of bile acid intermediates in urine was diminished. In patients with advanced liver disease (n = 4), cholic acid treatment resulted in increased levels of plasma transaminases, bilirubin and cholic acid with only a minor reduction in bile acid intermediates. CONCLUSIONS: Oral cholic acid therapy can be used in the majority of patients with a ZSD, leading to at least partial suppression of bile acid synthesis. However, caution is needed in patients with advanced liver disease due to possible hepatotoxic effects. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10545-016-9962-9) contains supplementary material, which is available to authorized users.